Case report and literature analysis: pancreatic hepatoid carcinoma with multiple lymph node metastases progressing to liver metastasis after pancreaticoduodenectomy - Huang, Xiaorui; Guo, Xinyi; Yu, Yahong (Frontiers in Oncology, 2024)
Hepatoid carcinoma is an extrahepatic primary tumor displaying characteristics reminiscent of hepatocellular carcinoma differentiation, which is found in various organs，such as the stomach, ovaries, gallbladder, and pancreas. Reports of pancreatic hepatoid carcinoma remain scarce. Consequently, understanding of this disease remains a priority, with no established consensus on its diagnosis and management. Here, we reported the case of a 45-year-old woman diagnosed with hepatoid carcinoma located in the pancreatic head, accompanied by multiple lymph node metastases. Following pancreaticoduodenectomy, the patient developed liver metastases within 3 months. Subsequently, she underwent adjuvant therapy consisting of Teysuno and Durvalumab following microwave ablation for the liver metastases. Remarkably, the patient has survived for one year without significant disease progression. This case underscores the potential efficacy of immunotherapy as a promising treatment option for pancreatic hepatoid carcinoma. Further research and clinical trials are warranted to explore the optimal management strategies for this rare and challenging malignancy.